Cathepsin gene expression in abdominal subcutaneous adipose tissue of obese/overweight humans - Qing Xu; Edwin C. M. Mariman; Gijs H. Goossens; Ellen E. Blaak; Johan W. E. Jocken (Adipocyte, 2020)
Cathepsin L1 (CTSL1) and B (CTSB) are lysosomal proteases, of which the expression and activity are impaired in adipose tissue (AT) of obese rodents, indicating AT lysosomal dysfunction. Here we assess the relation between abdominal subcutaneous AT (SCAT) CTSL1 and CTSB gene expression (qRT-PCR), body composition and tissue-specific insulin resistance in 77 overweight/obese (BMI: 225.6–38.6 kg/m2) well phenotyped men and women (61 M/16 F). A two-step hyperinsulinemic-euglycemic clamp was performed to assess AT, hepatic and skeletal muscle insulin sensitivity. Our data show that reduced CTSB expression is associated with markers of insulin resistance (standardized β = −0.561, p < 0.001), independent of adiposity, while CTSL1 expression is only associated with markers of body composition. Our data suggest the presence of lysosomal dysfunction in SCAT of obese humans with an impaired glucose homoeostasis. However, this needs to be investigated in more detail in future mechanistic studies.